The Effect of Price, Product Quality, and Brand Image on the Purchase Decision of OMG (Oh My Glam) Cosmetic Products Among Gen Z in Lamongan Sub-district - Melinda Okta Ramadhani; Dadang Wiratama; Ali Musta’in (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the influence of price, product quality, and brand image on purchasing decisions for OMG (Oh My Glam) cosmetic products among Generation Z in Lamongan District. The study uses a quantitative approach with explanatory research to analyze the relationship between the variables studied. The research sample consisted of 100 respondents selected using a purposive sampling technique. Data were collected through questionnaires with a Likert scale and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the help of SmartPLS 4.0 software. The results of the study indicate that partially, price has a positive and significant influence on purchasing decisions. Meanwhile, product quality shows a negative and insignificant influence on purchasing decisions. Brand image is proven to have a positive and significant influence on purchasing decisions. In addition to partial testing, the analysis results also show that price, product quality, and brand image simultaneously have a positive and significant influence on purchasing decisions for OMG (Oh My Glam) cosmetic products among Generation Z in Lamongan Sub-district.